2022
DOI: 10.3389/fncel.2022.893030
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 Deficiency Impairs Memory and Alters Oxylipins and Inflammatory Cytokines Without Affecting Cerebral Blood Flow in a High-Fat Diet Mouse Model of Cognitive Impairment

Abstract: Vascular cognitive impairment (VCI) is the second most common cause of dementia. There is no treatment for VCI, in part due to a lack of understanding of the underlying mechanisms. The G-protein coupled receptor 39 (GPR39) is regulated by arachidonic acid (AA)-derived oxylipins that have been implicated in VCI. Furthermore, GPR39 is increased in microglia of post mortem human brains with VCI. Carriers of homozygous GPR39 SNPs have a higher burden of white matter hyperintensity, an MRI marker of VCI. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(74 reference statements)
0
5
0
Order By: Relevance
“… 78 , 79 In addition, a high‐fat diet and a standard diet exhibit impaired spatial memory in the absence of GPR39. 80 Moreover, GPR39 regulates oxygen lipid synthesis, and GPR39 deletion induces the AA COX metabolites PGE2 and PGD2, 15‐keto PGF2a, and DHA 12/15‐LOX metabolite resolvin D1, indicating that constitutive GPR39 activity suppresses COX and 12/15‐LOX. These oxygenated lipid synthases and GPR39 may serve as biomarkers or targets for VCI therapy.…”
Section: Signaling Pathways Associated With Znr / ...mentioning
confidence: 99%
See 2 more Smart Citations
“… 78 , 79 In addition, a high‐fat diet and a standard diet exhibit impaired spatial memory in the absence of GPR39. 80 Moreover, GPR39 regulates oxygen lipid synthesis, and GPR39 deletion induces the AA COX metabolites PGE2 and PGD2, 15‐keto PGF2a, and DHA 12/15‐LOX metabolite resolvin D1, indicating that constitutive GPR39 activity suppresses COX and 12/15‐LOX. These oxygenated lipid synthases and GPR39 may serve as biomarkers or targets for VCI therapy.…”
Section: Signaling Pathways Associated With Znr / ...mentioning
confidence: 99%
“…These oxygenated lipid synthases and GPR39 may serve as biomarkers or targets for VCI therapy. 80 At present, many studies have reported on the relationship between zinc and dementia, but there are still controversies. Although most studies suggest that zinc is beneficial, some scholars still believe that zinc has neurotoxicity, which may be explained by the different binding sites between different concentrations of zinc and APP.…”
Section: Dementia: Gpr39 Deficiency Associated With Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxylipin profiling has utility for assessing oxidative stress, inflammatory status, and disease risk (Bah et al., 2022; Karu et al., 2022; Le et al., 2021). Generally, oxylipins derived from arachidonic acids, commonly referred as eicosanoids, are considered pro‐inflammatory lipid mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Because our previously described methodology requires chemical synthesis of (labeled) mercapturic acid metabolites that are not commercially available, these oxylipin metabolites never gained great popularity as biomarkers of oxidative stress. In recent years, our laboratory adapted and validated measurement of semi‐stable oxylipins, many of which are now commercially available and for which data have become increasingly available in the literature for comparison purposes (Bah et al., 2022; Le et al., 2021). However, accurate and precise quantification of oxylipins derived from arachidonic acid (AA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) remains challenging due to their very low levels in the body, their chemical stability, and issues with recovery from biological samples.…”
Section: Introductionmentioning
confidence: 99%